The Effect of N-Acetylcysteine on Creatinine Measurement: Protocol for a Systematic Review. Issue 1 (September 2018) - Huang, Johnny W.; Clarkin, Owen J.; McCudden, Christopher; Akbari, Ayub; Chow, Benjamin J. W.; Shabana, Wael; Kanji, Salmaan; Davis, Alexandra; Hiremath, Swapnil
Background: N-acetylcysteine (NAC) is an antioxidant which can regenerate glutathione and is primarily used for acetaminophen overdose. It is also a potential therapy to prevent iatrogenic acute kidney injury or slow the progression of chronic kidney disease. It has been considered in this context by many studies with mixed results. Notably, a biological-mechanism rationale for a protective effect of NAC has never been adequately reported. Among conflicting reports, there appears to be evidence that NAC may artificially lower measured serum creatinine without improving kidney function, potentially by assay interference. Given these mixed results, a systematic review of the literature will be conducted to determine whether there is an effect of NAC on kidney function measured with serum creatinine. Objective: To determine the effect of NAC on kidney function. Design: A systematic review and meta-analysis. Settings: Prospective studies, with administration of NAC, in the absence of any other change in kidney function (such as contrast administration or surgery). Patients: Adult humans aged 18 years old or more, either healthy volunteers or with chronic kidney disease, were administered with NAC. Populations having little to no kidney function such as in end-stage kidney disease will be excluded. Measurements: Serum creatinine and/or cystatin C measurements before and after NAC administration. Methods: An information specialist will assist in searching MEDLINE, EMBASE, and the Cochrane CENTRAL databases to identify all study types including randomized controlled trials, and prospective cohort studies reporting change in serum creatinine after NAC administration. Two reviewers will independently screen the titles and abstracts of the studies obtained from the search using predefined inclusion criteria and will then extract data from the full texts of selected studies. The weighted mean difference will be calculated for change in creatinine with NAC, using random-effects analysis. Quality assessment will be done with the Cochrane Risk of Bias tool for randomized trials and the Newcastle-Ottawa Scale for observational studies. Results: The outcome of interest is kidney function as reported by either change in serum creatinine and/or serum cystatin C measurement for randomized trials or comparing baseline (pre-NAC dose) values and those following the NAC dose. Limitations: Possible heterogeneity and publication bias and lack of mechanistic data. Conclusions: This systematic review will provide a synthesis of current evidence on the effect of NAC on serum creatinine measurement. These findings will provide clinicians with guidelines and serve as a strong research base for future studies in this field. Systematic review registration: This review is registered with PROSPERO, CRD42017055984